Heliograph Imaging Based on Total Variation Constraint and Nonlocal Operator. (19th February 2014) - Wang, S. Z.; Xu, L. Y.; Wang, Y.; Zhang, X. P.
Abstract : Heliograph imaging is the process to reconstruct the solar image from sparse frequency domain data, and compressed sensing (CS) algorithm has shown potential power to accurately recover images from highly undersampled data. However, the available compressed sensing based models available for heliograph imaging are not able to reconstruct fine solar structures and often suffer from undesired convolutive artifacts. This paper presents an imaging model with total variation constraint and nonlocal operator based on compressed sensing theory, with particular objective to suppress convolutive artifacts and reconstruct fine structures. In particular, an efficient algorithm is presented to solve the formulated model. Finally, a set of simulations has been conducted by using both synthetic and real images, and the results demonstrate that our proposed algorithm has surprisingly lower reconstruction errors than other methods.